THE INFLUENCE OF HUSBAND’S ACCOMPANYING ON THE INTENSITY OF ANXIETY IN THE DELIVERY PROCESS OF PRIMIGRAVIDA MOTHERS 1ST TIME AT PMB RINI DELI SERDANG IN 2023: THE INFLUENCE OF HUSBAND’S ACCOMPANYING ON THE INTENSITY OF ANXIETY IN THE DELIVERY PROCESS OF PRIMIGRAVIDA MOTHERS 1ST TIME AT PMB RINI DELI SERDANG IN 2023 - Simanullang, Ester; Ratna Sari Sembiring; Lisa Putri Utami Damanik (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Apart from being impatient to see your baby being born into the world, fear and anxiety about the birthing process are raging in your mind. Based on 2020 World Health Organization data, there were 216 maternal deaths per 100,000 live births due to complications of pregnancy and childbirth. Meanwhile, the maternal mortality rate in developing countries reaches 239 per 100,000 live births, 20 times higher than in developed countries. The anxiety experienced by mothers in labor will increase over time as contractions in the abdomen become more frequent so that this situation will create stress for the mother during labor. The psychological stress experienced by mothers when giving birth causes increased pain and anxiety. The type of research used in this research is observational analytical research with a cross sectional approach. The location of this research was the PMB Rini Deli Serdang. This research starts from the preparation of the thesis to the research plan from April to June 2023. The sample used in this research was all 38 primigravida mothers who gave birth at PMB Rini Deli Serdang. The data used in this research are primary data and secondary data. Data analysis is univariate and bivariate analysis data which is then processed using the SPSS 22.0 for Windows program. Through research classification data, it is known that the majority of respondents are >24 years old, namely 15 respondents (39.47%), the education level of junior high school respondents is 18 respondents (47.37%), the majority are not working, 30 respondents (78.95%). The results of the research showed that the majority (50.63%) of first-stage mothers experienced mild anxiety, and it was known that the majority (81.58%) of first-stage mothers received good support from their husbands. Through this research, it is hoped that health services can facilitate assistance to husbands and families during the first stage of labor and pay more attention to the anxiety of mothers in the first stage of labor